"The Role of Talk Shows in Islamic Parties Satellite Channels in Prioritizing National Issues for the Iraqi Public Viewers " - Hussein Ameer Abass \ Adel Abd-Alrazak Mostaf ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2024)
The Present research Delve in to the nature of the role that the Talk shows programs of the Islamic parties satellite channels in shaping the priorities of the Iraqi viewers towards national issues. The research aims to understand the reasons for the audience's preference for Talk shows programs on Islamic satellite parties channels, as well as to identify the key national issues followed by the audience through these programs. In adulation, it aims to uncover the in fluential factors of the formation of priorities and attitudes towards national issues among the participants.The researcher employed a field survey method, using a questionnaire method to achieve the research objectives. The sample size consisted of 600 participants from Baghdad province.